Strategi Membangun Citra Rumah Sakit Adhyaksa Jawa Timur melalui Media Sosial: Studi Kasus pada Akun Instagram @Rsadhyaksajatim dan Tiktok @Rsadhyaksa.Jatim - Muhammad Zacky Rasyadian; Ratna Setyarahajoe; Muhammad Fadeli (JURNAL ILMIAH SAINS TEKNOLOGI DAN INFORMASI, 2026)
In the digital era, social media has become an important communication strategy for organizations, including hospitals, in building and strengthening institutional image. Adhyaksa East Java Hospital utilizes Instagram and TikTok platforms as communication channels to disseminate health information, provide educational content, and establish relationships with the public. This study aims to describe and analyze social media communication strategies implemented through the accounts @rsadhyaksajatim and @rsadhyaksa.jatim in building the hospital’s image. This research employed a qualitative descriptive method, with data collected through observation, in-depth interviews, and documentation. The data were analyzed using the interactive model of Miles, Huberman, and Saldana, consisting of data reduction, data display, and conclusion drawing. The findings indicate that social media plays a strategic role in shaping the hospital image through informative, educational, and communicative content. The effectiveness of the strategy is supported by content consistency, attractive visual presentation, and active audience interaction. Engagement levels between the hospital and social media users serve as important factors in strengthening public trust and creating a positive perception of the institution. This study highlights the importance of optimizing digital communication strategies to support sustainable hospital branding in the digital era.